Humiliation and Greek debt - Smith, Dennis (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2017)
This article, the basis of a talk to the Hellenic Political Science Association in March 2012, presents an approach to the analysis of humiliation or forced social displacement. It makes reference to the particular example of Greece during the sovereign debt crisis and offers a comparison with the effects of Hurricane Katrina on New Orleans. Distinctions are made between yielding responses and challenging responses to humiliation, including escape and acceptance in the first category, and resistance-rejection, revenge-rejection and conciliation-reform in the latter category.